PENGARUH PEMBERIAN BIOCHAR KULIT KOPI DAN KOTORAN AYAM TERHADAP BEBERAPA SIFAT KIMIA ULTISOL DAN HASIL KACANG TANAH - Indriani, Atika; Wiskandar; Farni, Yulfita (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2026)
Ultisol is a type of soil that has a low pH, high aluminum saturation, and low nutrient content. This study aims to examine the effect of coffee husk biochar and chicken manure on the chemical properties of Ultisol and determine the optimal dose to increase peanut yield. The study used a Randomized Block Design (RBD), with six levels of treatment (B0: Control; B1: 15 t ha-1 Biochar; B2: 10 t ha-1 Biochar + 5 t ha-1 Chicken Manure; B3: 7.5 t ha-1 Biochar + 7.5 t ha-1 Chicken Manure; B4: 5 t ha-1 Biochar + 10 t ha-1 Chicken Manure; B5: 15 t ha-1 Chicken Manure), replicated four times. The observed parameters included soil pH, Organic-C, Available-P, and peanut dry seed yield. The data were analyzed using ANOVA and continued with the Duncan Multiple Range Test (DMRT) at the level of 5%. The results of the study showed that the application of coffee husk biochar and chicken manure had a significant effect on improving the chemical properties of Ultisol, such as increasing soil pH to 5.80 (B4), Organic-C to 3.00% (B2), and increased the Available-P to 35.31 ppm (B4). In addition, in the B3 and B4 treatments, the seed yield increased by 4.20 and 4.22 t ha-1. The recommended optimum dose is a combination of 7.5 t ha-1 of coffee husk biochar and 7.5 t ha-1 of chicken manure (B3).